Macrophage STING signaling promotes fibrosis in benign airway stenosis via an IL6-STAT3 pathway - YiLin Chen; ChengCheng Yang; YuShan Miao; DongChen Shi; Xiang Li; Sen Tian; YiFei Zhang; ChengFei Xu; YuChao Dong; ChaoFeng Han; Hui Shi; Chong Bai (Nature Communications)
Abstract Acute and chronic inflammation are important pathologies of benign airway stenosis (BAS) fibrosis, which is a frequent complication of critically ill patients. cGAS-STING signalling has an important role in inflammation and fibrosis, yet the function of STING in BAS remains unclear. Here we demonstrate using scRNA sequencing that cGAS‒STING signalling is involved in BAS, which is accompanied by increased dsDNA, expression and activation of STING. STING inhibition or deficiency effectively alleviates tracheal fibrosis of BAS mice by decreasing both acute and chronic inflammation. Macrophage depletion also effectively ameliorates BAS. Mechanistically, dsDNA from damaged epithelial cells activates the cGAS-STING pathway of macrophages and induces IL-6 to activate STAT3 and promote fibrosis. In summary, the present results suggest that cGAS-STING signalling induces acute inflammation and amplifies the chronic inflammation and tracheal fibrosis associated with benign airway stenosis, highlighting the mechanism and potential drug target of BAS.